RESPONS PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) PADA BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR NASA - Febrianto Febrianto; Nur Hayati (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
Lettuce (Lactuca sativa L.) is a leafy vegetabke with a high economic value and offers consumers a number of advantages in Indonesia. The effect of using inorganic fertilizers over a long period of time, causing reduced soil productivity, has made the use of organic fertilizers more optimal nowadays. The purpose of the study was to determine the effect of various liquid organic fertilizer Nasa on lettuce growth and yields. The research was conducte in Sintuwu village Palolo sub district Sigi district from August to September 2020. A Randomize Block design was used with treatment consisting of no fertilizer added (N0), 1.5 l/l water. The purpose of this study was to determine the response of various concentrations of liquid organic fertilizer NASA on the growth and yield of lettuce. The implementation of this research from August to September 2020, on agricultural land in Sintuwu Village, Palolo District, Sigi Regency. This study was structured using a Randomized Block Design (RAK), which consisted of 5 treatments and 4 replications in order to obtain 20 experimental units. Concentration of liquid organic fertilizer used as treatment: No= control, N1=1.5 ml/1 water, N2=3.0 ml/1 water, N3=4.5 ml/1 water, N4=6 ml/1 water . Each experimental unit consisted of 48 plants, so a total of 960 plants. The results of this study indicate that the concentration of liquid organic fertilizer NASA does not have a significant effect on all observations, but there is a tendency for treatment with a concentration of 1.5 ml/1 water to show higher yields on the average plant height (5.97 cm). , number of leaves (7.00 leaves), leaf area (61.79 cm), fresh weight (8.95 g) and root length (8.98 cm).